[The issue of the rule of law in West Africa] : [comparative analysis of the situation of Côte d'Ivoire, Mauritania, Liberia and Sierra Leone] - (:unkn) unknown (My University, 2009)
The question of the Rule of law arises more and more with much acuity in Africa in general and in West Africa in particular. The observable deficit of Rule of law in certain countries of this region is one of the root causes of belligerence and crisis with dramatic consequences: violation of Human rights, desinstitutionalization, refusal of democratic alternation, impunity, poverty, insecurity, etc…Côte d’Ivoire, Mauritania, Liberia, and Sierra Leone are not immune to this. These countries are characterized by particular situations in the light of the crisis they encounter and have encountered, as well as common issues in the long and difficult quest for the establishment of the Rule of Law. This process, with major obstacles, gives rise to a real normative production with the combined intervention of the regional, pan African and international communities. And provided, the “conflict of norms” are not to be excluded. Hence the need to consider prospects for resolving crises, to establish the Rule of law in West Africa.
Keywords: African Research